„Lernen durch Spielen“ in der Lernwerkstatt – In analogen und digitalen Lern- und Spielräumen - Kottmann, Brigitte; Letmathe-Henkel, Birte; Wohnhas, Verena (Hochschullernwerkstätten im analogen und digitalen Raum. Perspektiven auf Didaktik und Forschung in innovativen Lernsettings)

Zwischen Unterstützung und Herausforderung. Perspektiven auf die Arbeitsbeziehung von Lehramtsanwärter:innen und ihren Mentor:innen im Vorbereitungsdienst. - Ellersiek, Annchristin; Kottmann, Brigitte (Grundschule aktuell)

Kulturelle Teilhabe und innovative Preiskonzepte. Einblicke in ein interdisziplinäres Forschungsprojekt - Flath, Beate; Kundisch, Dennis; Wunderlich, Nancy

Autobiographisches Philosophieren in Schule und Hochschule

Strafe, Zeitschrift für Didaktik der Philosophie und Ethik

Jeremy Benthams Panoptikum. Ein strittiges Meisterstück zum Philosophieren mit Architektur und Puppen - Albus, Vanessa (ZDPE)

Strafen mit Fußabstimmung. Ein Weg zur Gestaltung des philosophischen Kanons - Albus, Vanessa (ZDPE)

Einleitung - Albus, Vanessa (Autobiographisches Philosophieren in Schule und Hochschule)

In Search of Partitioning Oracle Attacks Against TLS Session Tickets - Radoy, Maximilian Manfred; Hebrok, Sven Niclas; Somorovsky, Juraj (Lecture Notes in Computer Science)

A User Study Evaluating Argumentative Explanations in Diagnostic Decision Support - Liedeker, Felix; Sanchez-Graillet, Olivia; Seidler, Moana; Brandt, Christian; Wellmer, Jörg; Cimiano, Philipp
As the field of healthcare increasingly adopts artificial intelligence, it becomes important to understand which types of explanations increase transparency and empower users to develop confidence and trust in the predictions made by machine learning (ML) systems. In shared decision-making scenarios where doctors cooperate with ML systems to reach an appropriate decision, establishing mutual trust is crucial. In this paper, we explore different approaches to generating explanations in eXplainable AI (XAI) and make their underlying arguments explicit so that they can be evaluated by medical experts. In particular, we present the findings of a user study conducted with physicians to investigate their perceptions of various types of AI-generated explanations in the context of diagnostic decision support. The study aims to identify the most effective and useful explanations that enhance the diagnostic process. In the study, medical doctors filled out a survey to assess different types of explanations. Further, an interview was carried out post-survey to gain qualitative insights on the requirements of explanations incorporated in diagnostic decision support. Overall, the insights gained from this study contribute to understanding the types of explanations that are most effective.

An Empirical Investigation of Users' Assessment of XAI Explanations: Identifying the Sweet-Spot of Explanation Complexity - Liedeker, Felix; Düsing, Christoph; Nieveler, Marcel; Cimiano, Philipp
While the importance of explainable artificial intelligence in high-stakes decision-making is widely recognized in existing literature, empirical studies assessing users' perceived value of explanations are scarce. In this paper, we aim to address this shortcoming by conducting an empirical study focused on measuring the perceived value of the following types of explanations: plain explanations based on feature attribution, counterfactual explanations and complex counterfactual explanations. We measure an explanation's value using five dimensions: perceived accuracy, understandability, plausibility, sufficiency of detail, and user satisfaction. Our findings indicate a sweet spot of explanation complexity, with both dimensional and structural complexity positively impacting the perceived value up to a certain threshold.
Keywords: XAI; Explanation Complexity; User Perception

Verantwortung - Höper, Lukas; Schulte, Carsten; Benzmüller, Christoph (Künstliche Intelligenz für Lehrkräfte)

Reasoning in Rough Description Logics with Multiple Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Rules and Reasoning - 8th International Joint Conference, RuleML+RR 2024, Bucharest, Romania, September 16-18, 2024, Proceedings)

A conductivity-based flow imaging sensor for the investigation of liquid flow dynamics in stationary and moving separation columns packed with Mellapak 250Y - Mamedov, Tural; Ehlert, Thomas; Schleicher, Eckhard; Dias, Felipe D. A.; Schubert, Markus; Kenig, Eugeny Y.; Hampel, Uwe

Critically 3-frustrated signed graphs - Cappello, Chiara; Naserasr, Reza; Steffen, Eckhard; Wang, Zhouningxin (Discrete Mathematics)

Curvature and stability of quasi-geostrophic motion - Suri, Ali (Journal of Geometry and Physics)

Conjugate points along spherical harmonics - Suri, Ali (Journal of Geometry and Physics)

L^1-regularity of strong ILB-Lie groups - Glöckner, Helge; Suri, Ali

Reasoning in Rough Description Logics with Multiple Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Rules and Reasoning - Eighth International Joint Conference, RuleML+RR 2024, Proceedings)

On German Comics Traditions: An Explorative Approach to Digital Comics Historiography - Giesa, Felix; Hartel, Rita; Dunst, Alexander (Comics | Histories)